2016
DOI: 10.4306/pi.2016.13.5.473
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Incidence and Predictors of Cognitive Impairment among Older Koreans: Findings from a 6-Year Prospective Cohort Study

Abstract: ObjectiveThis study investigated gender-specific incidence and predictors of cognitive impairment among community-dwelling older adults in South Korea.MethodsUsing data from the 2006 and 2012 Korean Longitudinal Study of Ageing (KLoSA), 925 females and 834 males aged 65 and over without cognitive impairment at 2006 were analyzed separately. Cognitive impairment was measured based on the Korean version of the Mini-Mental State Exam (K-MMSE) normative score. Generalized Estimating Equations (GEE) was conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 33 publications
6
48
1
Order By: Relevance
“…Of these, those with estimates that could not be combined, that were not cohort-designed, and those which used estimates other than odds ratio (OR), relative risk (RR), and hazard ratio (HR), were also omitted at this stage. Finally, eleven studies 9 , 14 , 20 , 21 , 24 , 29 34 were included, seven of which 9 , 14 , 20 , 24 , 29 31 were combined in the following meta-analyses. Eight studies 20 , 21 , 24 , 29 , 31 34 were analyzed in meta-regression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, those with estimates that could not be combined, that were not cohort-designed, and those which used estimates other than odds ratio (OR), relative risk (RR), and hazard ratio (HR), were also omitted at this stage. Finally, eleven studies 9 , 14 , 20 , 21 , 24 , 29 34 were included, seven of which 9 , 14 , 20 , 24 , 29 31 were combined in the following meta-analyses. Eight studies 20 , 21 , 24 , 29 , 31 34 were analyzed in meta-regression.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven related studies were enrolled into the present study. All prospective cohort studies included participants across Europe 32 , North America 14 , 20 , 21 , 29 31 , 33 , Oceania 9 , 24 , and Asia 34 . All cohorts, except for one 21 , included both genders.…”
Section: Resultsmentioning
confidence: 99%
“…People who regularly exercise have been shown to maintain better cognitive function than those who do not in both the current study and previous research. 7 Regular exercise may help prevent physical diseases such as cardiovascular disease-a risk factor for cognitive impairment-and consequently contribute to the maintenance of cognitive function. 53 Previous studies have reported the impact of BMI or obesity on cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial research has explored the risks and protective factors of cognitive impairment. Based on previous studies, the following are all closely associated with cognitive impairment: sociodemographic variables such as age, education, and marital status 3,4 ; physical conditions and diseases such as high blood pressure, diabetes, and cardiovascular disorders [4][5][6] ; health-related behaviours such as smoking, alcohol consumption, and regular exercise 7,8 ; physical function 9,10 ; and social participation involving, for example, social gatherings, religious activities, and volunteer work. 11,12 As individuals age, the risk of physiological diseases increases, and such diseases and conditions that are common among the elderly, such as high blood pressure, diabetes, and stroke, may be associated with cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation